2016
DOI: 10.21566/tarbitderg.280162
|View full text |Cite
|
Sign up to set email alerts
|

Melez Mısır Islahında In-Vivo Katlanmış Haploid Tekniğinde Kullanılan Farklı Inducer Genotiplerin Haploid İndirgeme Oranların Belirlenmesi

Abstract: ÖzBu çalışma melez mısır ıslahında in-vivo katlanmış haploid hatların elde edilmesi çalışmasında kullanılan farklı induzer genotiplerin haploid indirgeme oranlarının tespit edilmesi amacıyla 2014 yılında Doğu Akdeniz Tarımsal Araştırma Enstitüsü'nde yürütülmüştür. Çalışmada induzer olarak (haploid indirgeyici ve toz verici) RWS, RWK-76 hatları ile bu hatların melezi olan RWS X RWK-76 melezi ve Stock-6 hattı kullanılmıştır. Haploid tohum elde etmek amacıyla ana (toz alıcı) olarak, toplamda 75 farklı genotip kul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Cengiz (2016) reported that the highest HIR was established as 20.42% in the RWK-76 inducer line and that the lowest HIR was calculated as 17.75% in WS14. Cerit at al (2016) reported that the RWK-76 has highest HIR and the lowest one is Stock-6. Dang et al (2011) reported that the rates of putative haploids among progenies induced with the inducer lines RWK76 and RWK-76xRWS (15.7 and 15.0%, on average, respectively) were significantly lower (P<0.05) than those observed with the inducer line RWS (23.8%) for the same maternal plant material.…”
Section: Haploid ıNduction Rate (Hir)mentioning
confidence: 99%
“…Cengiz (2016) reported that the highest HIR was established as 20.42% in the RWK-76 inducer line and that the lowest HIR was calculated as 17.75% in WS14. Cerit at al (2016) reported that the RWK-76 has highest HIR and the lowest one is Stock-6. Dang et al (2011) reported that the rates of putative haploids among progenies induced with the inducer lines RWK76 and RWK-76xRWS (15.7 and 15.0%, on average, respectively) were significantly lower (P<0.05) than those observed with the inducer line RWS (23.8%) for the same maternal plant material.…”
Section: Haploid ıNduction Rate (Hir)mentioning
confidence: 99%
“…Not all inducers provide the same success, and they cannot be used in harmony with every donor (female parent) genotype. In fact, the induction rates achieved in studies using different numbers of donor materials showed a wide variation ranging from 7.1% to 12.8% (Cerit et al, 2016;Zararsız et al, 2019). These results demonstrate that donors and inducers play a key role in the in vivo doubled haploid technique.…”
Section: Introductionmentioning
confidence: 81%
“…HIR values for the in vivo maternal haploid technique varied between 2.8% and 12.8% in the scientific literature (Eder & Chalyk, 2002;Prigge et al, 2012;Cerit et al, 2016;Zararsız et al, 2019). It was emphasized that the HIR varies according to the donors and inducer lines used.…”
Section: Donor X Inducer Interaction On Success Of Haploid Inductionmentioning
confidence: 99%
“…Plant breeders have resorted to new technologies to shorten the time required to produce high-yielding and quality hybrid seeds. Techniques to obtain haploid plants provide significant advantages in shortening the seed breeding period [1]. The starting point of maize breeding programs is to produce homozygous lines that will provide hybrid diversity.…”
Section: Introductionmentioning
confidence: 99%